2019
DOI: 10.1097/dcr.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathogenic Germline Variants Among Patients With Advanced Colorectal Cancer Undergoing Tumor Genomic Profiling for Precision Medicine

Abstract: BACKGROUND: Genomic profiling of colorectal cancer aims to identify actionable somatic mutations, but can also discover incidental germline findings. OBJECTIVE: To report the detection of pathogenic germline variants that confer heritable cancer predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…A recent study of 46 genes in 151 patients with advanced colorectal cancer found 15 carriers of germline mutations. Among them, CHEK2 with four mutation carriers was the most frequently altered gene [ 240 ].…”
Section: Germline Chek2 Variantsmentioning
confidence: 99%
“…A recent study of 46 genes in 151 patients with advanced colorectal cancer found 15 carriers of germline mutations. Among them, CHEK2 with four mutation carriers was the most frequently altered gene [ 240 ].…”
Section: Germline Chek2 Variantsmentioning
confidence: 99%
“…Contrarily, another meta-analysis suggests that pathogenic variants in BRCA1 increase CRC risk (OR = 1.56) but not in BRCA2 [ 111 ]. Another gene that deserves attention in this section is TP53 , where pathogenic variants have been recurrently found in familial/early onset and unselected CRC patients [ 3 , 4 , 5 , 6 , 28 , 32 , 102 , 112 , 113 , 114 , 115 ]. As occurs with other non-CRC genes, the debate about TP53 ’s causal role in CRC predisposition is open for discussion.…”
Section: Non-crc Hereditary Cancer Genesmentioning
confidence: 99%
“…While estimates indicate that approximately 14% of all colorectal cancer (CRC) patients have at least one first-degree relative affected with the same tumor type [ 1 , 2 ], 4–8% of all CRC patients carry germline pathogenic variants in one of the known high penetrance genes for this tumor [ 3 , 4 , 5 , 6 ], with a relevant proportion of the familial aggregation of CRC remaining unexplained. The identification of a germline pathogenic variant in a colorectal cancer-predisposing gene has important consequences for the patients and their relatives, as they can be counseled and managed based on gene-specific guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,14 Studies suggest that 3% to 18% of patients undergoing tumor-normal sequencing have a pathogenic germline variant. [15][16][17][18][19] Although most patients are likely to be interested in secondary germline findings, current studies suggest that a subset of patients may prefer not to receive information about secondary germline findings. [20][21][22] Qualitative studies have reported patient concerns about receiving secondary germline information, such as the complexity of the information, potential negative emotional impact, additional burden in the setting of advanced cancer, concerns about sharing these results with relatives, and additional costs.…”
Section: Addressing the Potential For Secondary Germline Findingsmentioning
confidence: 83%